2021
DOI: 10.1177/0950017020980997
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Sexual Orientation in Britain

Abstract: Studies looking at patterns of labour market outcomes among lesbian, gay and bisexual (LGB) individuals focus mostly on earnings, while non-pecuniary outcomes of LGB individuals have remained a relatively under-researched area. Using the latest wave of the Workplace Employment Relations Study (WERS), this article investigates the job satisfaction levels of LGB individuals compared to their heterosexual peers for the first time in Britain. The results show significantly lower job satisfaction levels only for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Our study sought to assess the impact of the fear of COVID-19 and the negative impact of COVID-19 on WRQoL, through the lens of sexual orientation. Concerning WRQoL, previous literature has shown significant differences attributable to sexual orientation [49][50][51][52], with manifested lower levels of WRQoL in sexual minorities, and higher burnout levels [52,53]. Our results were similar, since significant differences were found among sexual orientations, favoring heterosexual participants with higher scores for all WRQoL variables over bisexual and gay or lesbian participants.…”
Section: Discussionsupporting
confidence: 83%
“…Our study sought to assess the impact of the fear of COVID-19 and the negative impact of COVID-19 on WRQoL, through the lens of sexual orientation. Concerning WRQoL, previous literature has shown significant differences attributable to sexual orientation [49][50][51][52], with manifested lower levels of WRQoL in sexual minorities, and higher burnout levels [52,53]. Our results were similar, since significant differences were found among sexual orientations, favoring heterosexual participants with higher scores for all WRQoL variables over bisexual and gay or lesbian participants.…”
Section: Discussionsupporting
confidence: 83%
“…Sweden, Canada, Australia, the Netherlands and the United Kingdom). Some work has shown that disadvantages are larger for bisexual individuals and younger individuals (Bayrakdar & King, 2021; Martell, 2019; Mize, 2016; Sabia, 2014, 2015). Recent research in the literature has found evidence that the wage differentials have been getting smaller over time (Carpenter & Eppink, 2017; Carpenter, 2008; Clarke & Arnold, 2018; Jepsen & Jepsen, 2021).…”
Section: Labour Market Effects Of Sexual Orientationmentioning
confidence: 99%
“…Following previous studies using intra-categorical intersectionality (McCall, 2005), we highlight three significant directions in research that can help to document a variety of experiences amongst LGBT individuals. The first requires separating categories of identity: L, G, B and T. For instance, research from the UK argues that bisexual individuals experience unique forms of discrimination and exclusion (Bayrakdar and King, 2021) and they are not only discriminated by heterosexuals but also by the other members of LGBT communities (Barker et al, 2012). Similarly, Meyer (2012) argues that LGBT research on hate crime has predominantly focused on homosexuality and heteronormativity and despite the evidence on gendered forms of anti-queer violence, most studies have overlooked the intersections of gender identity and sexual orientation in LGBT research.…”
Section: Theoretical Frameworkmentioning
confidence: 99%